Death by a Thousand 10-Minute Tasks: Workarounds and Noncompliance in University Research Administration. Issue 4 (April 2021) - Bozeman, Barry; Youtie, Jan; Jung, Jiwon
The article examines administrative workarounds in the context of university research administration. The empirical results from 116 semi-structured interviews with academic researchers with active National Science Foundation awards are framed by a "Rules Response" model positing relationships among rules compliance requests, administrative burden, red tape, and response choices, including compliance, appeal, rule bending, rule breaking, and workaround behaviors. Propositions are presented and reviewed in light of empirical results. The article concludes with implications of empirical results for improving the Rules Response model and a more general discussion of research needed to improve the understanding of both rules compliance and workarounds.